Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Connect with professionals on our platform to receive accurate answers to your questions quickly and efficiently. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

The function k(x) = (gx h)(x) is graphed below, where g is an exponential function and h is a linear function

The Function Kx Gx Hx Is Graphed Below Where G Is An Exponential Function And H Is A Linear Function class=

Sagot :

Given k(x)=g(h(x));

[tex]\begin{gathered} \text{But h(x)=x+1} \\ At\text{ x=-1, } \\ k(-1)=g(h(-1))=g(-1+1)=g(0) \end{gathered}[/tex]

Now, let's assess the options.

First,

[tex]\begin{gathered} g(x)=2^x \\ at\text{ x=0,} \\ g(0)=2^0=1\ldots\ldots\ldots\ldots\ldots wrong \end{gathered}[/tex]

Also,

[tex]\begin{gathered} g(x)=-2^x \\ g(0)=-2^0 \\ g(0)=-1\ldots\ldots\ldots\ldots\ldots\ldots\ldots\text{.correct} \end{gathered}[/tex]

The formular for g(x) is -2^x